A NOVEL DE NOVO LIKELY PATHOGENIC VARIANT OF WFS-1 GENE IN A PAKISTANI CHILD WITH NON-CLASSIC WFS-1 SPECTRUM DISORDER - Hanif, Misbah Iqbal; Ahmed, Hamza; Ibrahim , Mohsina Noor; Raza, Syed Jamal; Ahmed, Syed Ajaz (Journal of Ayub Medical College Abbottabad, 2024)
Wolfram syndrome is a progressive neurodegenerative disorder caused by an alteration in the WFS-1 gene, located on chromosome 4p16.1 and is characterized by the acronym DIDMOAD (Diabetes Insipidus, Diabetes Mellitus, Optic Atrophy, and Deafness). WFS-1 gene encodes for a transmembrane protein termed Wolframin found in the membrane of the endoplasmic reticulum. Although Wolfram Syndrome is generally considered an autosomal recessive disorder, a milder non-classic autosomal dominant form has been reported in association with a single pathogenic or likely pathogenic variant in WFS-1 gene. Objective was to date more than 200 variants have been identified in the WFS-1 gene. This case report aims to highlight and explain a novel de-novo likely pathogenic variant of the WFS-1 gene in a Pakistani child, which is highly plausible to induce non-classic WFS-1 spectrum disorder (MedGen UID: 481988). Case Discussion: Our patient, a seven-year-old boy, initially sought medical attention at our endocrine clinic for diabetic control. Besides diabetes, other notable features included short stature, sensorineural deafness and a history of bilateral cataracts. Family history was significant for parental consanguinity. A clinical diagnosis of Wolfram Syndrome was suspected and a multi gene panel test which included the WFS-1 gene was ordered. Initial report noted a variant of uncertain significance in the WFS-1 gene at c.2586G>T (p.Lys862Asn), which was later reclassified as a likely pathogenic variant by the laboratory based on the patient's clinical presentation. Conclusion: Access to genetic testing is not readily available in Pakistan and our population is under studied and these complex diagnoses are often missed. In this study, we present a novel de novo likely pathogenic variant in the WFS-1 gene that causes non-classic WFS-1 spectrum disorder in a child from our population.